2015
DOI: 10.1039/c5cc05755h
|View full text |Cite
|
Sign up to set email alerts
|

The power laws of nanoscale forces under ambient conditions

Abstract: We report a power law derived from experimental atomic force microscopy (AFM) data suggesting a nano to mesoscale transition in force-distance dependencies. Our results are in relative agreement with the Hamaker and Lifshitz theories for van der Waals forces for the larger tip radii only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…While WCA quanties the water wettability of a surface on a macroscopic length scale, the force of adhesion |F adh | (the attractive maximum of the force prole) measured/simulated by AFM provides an alternative measure on a nanoscopic scale. [66][67][68][69][70][71][72][73] A relation between the two quantities is highly needed, since it enables the high-resolution characterization of wettability. For this purpose, we examine the correlation between WCA and |F adh |.…”
Section: Resultsmentioning
confidence: 99%
“…While WCA quanties the water wettability of a surface on a macroscopic length scale, the force of adhesion |F adh | (the attractive maximum of the force prole) measured/simulated by AFM provides an alternative measure on a nanoscopic scale. [66][67][68][69][70][71][72][73] A relation between the two quantities is highly needed, since it enables the high-resolution characterization of wettability. For this purpose, we examine the correlation between WCA and |F adh |.…”
Section: Resultsmentioning
confidence: 99%
“…10 It is not clear whether more information can be extracted from the phenomena, that is, whether enhancing the resolution of the system would provide more information about the nanoscale properties of the surface or whether we have reached a point where data processing is the main bottleneck in terms of advancing in the field. 11,12 On the other hand, we have recently shown that simple power laws 13 are not enough to explain the rich phenomena that we have already probed in ambient conditions, where air contaminants, such as CO 2 and water, start adhering to the surface almost immediately after surfaces are produced. 14 This surface phenomenon under ambient conditions, which we term here "surface aging," is a dynamic process with many unknowns and possibly related to very complex physical processes such as ion exchange, surface energy dynamics, and surface-tension thermodynamic equilibrium, 15,16 thus providing us with a suitable candidate question in AFM.…”
mentioning
confidence: 93%
“…Each set corresponds to approximately 50 data points taken for these random sets (taken with several cantilevers with only constant being the time slot). A total of 56 sets similar to those shown in Table I (see the supplementary material) were employed to generate a library to monitor the HOPG aging process, i.e., an HOPG aging library; this library is simply our final optimized predictive model produced by our ANN, 7,13 and the selection and performance of the model library are discussed below. Figure 2 shows some of the force data and an TABLE I.…”
mentioning
confidence: 99%
“…Here we choose to measure the distances in the well of the FDC in a similar fashion to that recently proposed elsewhere by the authors 19,20 . The steps are as follows:…”
Section: Parametrizing Raw Data and Transformation Into Input Featuresmentioning
confidence: 99%
“…We note that by varying β from 0 to 1 any arbitrary force curve can be fully parameterized and quantified 19 for F<0 nN.…”
Section: Parametrizing Raw Data and Transformation Into Input Featuresmentioning
confidence: 99%